Imsnc761 and DDX6 synergistically suppress cell proliferation and promote apoptosis via p53 in testicular embryonal carcinoma cells. Issue 4 (3rd July 2018) - Duan, Zhengzheng; Ping, Ping; Wang, Guishuan; Zhang, Xiansheng; Sun, Fei
Abstract : Intermediate-sized non-coding RNAs (imsncRNAs) have been shown to play important regulatory roles in the development of several eukaryotic organisms. In the present research, we selected imsncRNA 761 (imsnc761) as a research target. Expression analyses in a previous study showed that imsnc761 was down-regulated in maturation-arrested testis tissues as compared with the level in normal controls. In the present study, we found that imsnc761 could interact with DEAD-box helicase 6 (DDX6) to induce NTERA-2 (NT2 (testicular embryonal carcinoma cell)) cell apoptosis and proliferation inhibition via the p53 pathway. This interaction between imsnc761 and DDX6 also inhibited mitochondrial function and specific gene transcription and translation. To facilitate further research, we used label-free quantitation method to analyze the associated differences in Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathways and biological processes. This confirmed the changes in several specific pathways, which matched our molecular experimental results.